2015
DOI: 10.1111/dme.12696
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of circulating betatrophin concentrations with insulin secretion capacity, evaluated by glucagon stimulation tests

Abstract: AimTo investigate the relationship between plasma betatrophin concentrations and insulin secretion capacity in people with Type 2 diabetes.MethodsGlucagon stimulation tests (1 mg) were performed in 70 people with Type 2 diabetes after an overnight fast. Plasma betatrophin concentrations were measured using an enzyme‐linked immunosorbent assay. Insulin secretion capacity was evaluated by measuring increments of C‐peptide concentration in response to glucagon stimulation, and creatinine clearance was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…Betatrophin positively correlated with age in the controls and with HbA1c in type 2 diabetes patients [21,22]. In addition, plasma betatrophin concentrations in diabetes patients were positively correlated with duration of Type 2 diabetes and negatively correlated with increments of C-peptide concentration and creatinine clearance [40]. However, one recent study showed betatrophin and irisin were not associated with β-cell function in previously diagnosed T2DM patients [41].…”
Section: Discussionmentioning
confidence: 96%
“…Betatrophin positively correlated with age in the controls and with HbA1c in type 2 diabetes patients [21,22]. In addition, plasma betatrophin concentrations in diabetes patients were positively correlated with duration of Type 2 diabetes and negatively correlated with increments of C-peptide concentration and creatinine clearance [40]. However, one recent study showed betatrophin and irisin were not associated with β-cell function in previously diagnosed T2DM patients [41].…”
Section: Discussionmentioning
confidence: 96%
“…However, there was no correlation between betatrophin and fasting glucose, insulin, HbA1c, TAGs, total cholesterol or LDL-C [67]. In T2DM, many investigators showed that level of betatrophin was positively correlated with age [60,68], diabetes duration [62,68], HbA1c [56,58,60], total cholesterol and LDL-C [59,65], HDL-C [59,63], TAGs [60], BMI in female only [61], glucose [60,66], and HOMA-IR [57,59]. Contrarily, Abu-Farha et al (2015) found a negative correlation between betatrophin and total cholesterol and LDL-C [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation was not present in T2D patients [15]. In other studies, serum betatrophin concentrations inversely correlated with the increment of C-peptide in the glucagon stimulation test in T2D patients [21]. This might indicate that the increase in serum betatrophin concentrations is a result of insulin resistance observed in obese nondiabetic subjects.…”
Section: Introductionmentioning
confidence: 86%